The Relationship Between Corporate Social Responsibility and Financial Performance: Empirical Evidence from Real Estate Firms in China - TAN, TIANHE (2019)
n recent years, China's real estate industry has become a pillar industry of the national economy. The development of the real estate industry cannot only promote the development of related industries, but also promote the prosperity of the economy. As a part of the social group, real estate firms’ development is taken from the society. Giving back to society is an obligation as well as a right. Therefore, studying the relationship between corporate social responsibility (CSR) and financial performance cannot only provide a solid basis for real estate firms to fulfil CSR but also enable relevant theoretical research to be improved. This paper aims to examine the impact of CSR on financial performance in the real estate industry. Based on stakeholder theory and social contract theory, this paper selects 92 real estate enterprises' data from 2014-2018 as research sample, proposes hypotheses and constructs panel, regression models. The paper uses HEXUN CSR score to measure CSR performance, measures the financial performance with ROA and Tobin’s Q. Research results show that fulfilling CSR can improve financial performance. Significantly, fulfilling shareholders’ responsibility and customers’ responsibility are positively related to financial performance. Fulfilling environmental responsibility does not improve financial performance. Additionally, fulfilling employees’ responsibility only have a positive impact on financial performance in the short term and has no impact in the long run. Besides, it should also be noted that CSR has a lag effect on financial performance. Keywords: CSR, financial performance, stakeholder theory